Energy-efficient computing and data centers - Brochard, Luigi; Kamath, Vinod; e uthor; Holland, Scott; Mittelbach, Walter; Ott, Michael, 1977- (London : ISTE, Ltd. ; Hoboken : John Wiley & Sons, Incorporated, 2019)
Data centers consume roughly 1% of the total electricity demand, while ICT as a whole consumes around 10%. Demand is growing exponentially and, left unchecked, will grow to an estimated increase of 20% or more by 2030. This book covers the energy consumption and minimization of the different data center components when running real workloads, taking into account the types of instructions executed by the servers. It presents the different air- and liquid-cooled technologies for servers and data centers with some real examples, including waste heat reuse through adsorption chillers, as well as the hardware and software used to measure, model and control energy. It computes and compares the Power Usage Effectiveness and the Total Cost of Ownership of new and existing data centers with different cooling designs, including free cooling and waste heat reuse leading to the Energy Reuse Effectiveness. The book concludes by demonstrating how a well-designed data center reusing waste heat to produce chilled water can reduce energy consumption by roughly 50%, and how renewable energy can be used to create net-zero energy data centers.
Systems in data centers -- Cooling servers -- Cooling the data center -- Power consumption of servers and workloads -- Power and performance of workloads -- Monitoring and controlling power and performance of servers and data centers -- PUE, ERE and TCO of various cooling solutions.
Print version record.
Includes bibliographical references and index.
John Wiley and Sons
Keywords: Data centers -- Energy consumption; Centres de traitement de l'information; COMPUTERS -- Information Technology